Relationship of Dermatoglyphics with Dental Caries among Pre-School Children- A Hospital Based Study - Shah, Priyanka; Khanal, Sanskriti (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Dermatoglyphics is the study of the intricate dermal ridge patterns on the skin covering the palmar and plantar surfaces of hand and feet. The basis of considering dermatoglyphic patterns as genetic marker for dental caries is that the epithelium of finger buds as well as enamel has ectodermal origin, and both develop at the same time of intrauterine life. Methods This study was conducted to examine the relationship ofdermatoglyphics with dental caries among 310 childrenaged 2-6 year old in a private dental hospital in Kathmandu, Nepal. The prevalence of caries was recorded using “Dentition status and treatment needs” (WHO basic oral health assessment form, 1997). They were divided into three groups as follows: Group I (dmft score =0–2), Group II (dmft score = 3–4) and Group III (dmft score ≥5). Black duplicating ink was used to record finger prints (both right and left hand) of all the subjects .The frequency of occurrence of type of dermatoglyphic pattern on fingertip of each digit was noted. Results No statistically significant association was seen between dermatoglyphic pattern and dental caries in right hand. Statistically significant association was seen between dermatoglyphic pattern and dental caries in 3rd digit of left hand (P-value <0.05). Conclusions Dermatoglyphics serves as a diagnostic tool in predicting dental caries at an early age and hence preventive treatment strategies can be planned.